The Empirics of Social Capital and Economic Development: A Critical Perspective - Fabio Sabatini (Fondazione Eni Enrico Mattei (FEEM), 2006)
This paper provides an introduction to the concept of social capital, and carries out a critical review of the empirical literature on social capital and economic development. The survey points out six main weaknesses affecting the empirics of social capital. Identified weaknesses are then used to analyze, in a critical perspective, some prominent empirical studies and new interesting researches published in the last two years. The need emerges to acknowledge, also within the empirical research, the multidimensional, context-dependent and dynamic nature of social capital. The survey also underlines that, although it has gained a certain popularity in the empirical research, the use of indirect indicators may be misleading. Such measures do not represent social capitals key components identified by the theoretical literature, and their use causes a considerable confusion about what social capital is, as distinct from its outcomes, and what the relationship between social capital and its outcomes may be. Research reliant upon an outcome of social capital as an indicator of it will necessarily find social capital to be related to that outcome. This paper suggests to focus the empirical research firstly on the structural aspects of the concept, therefore excluding by the measurement toolbox all indicators referring to social capitals supposed outcomes.
Keywords: A12; A13; A31; O10; Z13; 330; Social capital; Social networks; Trust; Economic development; Relation of economics to other disciplines; Relation of economics to social values